Spermatic cord leiomyosarcoma in a young male: a case report and literature review - Nadeem, Muhammad Sohaib; Kashif Ali Sarwar; Ujala Ali (Journal of the Pakistan Medical Association, 2022)
Spermatic cord Leiomyosarcoma is an extremely rare intrascrotal tumour. Owing to its rarity, no definitive management guidelines have been formulated as yet. The majority of published literature comprises of case reports or case series and show varying outcomes depending upon multiple patient- and disease-related factors. Almost all cases are older adults with majority in the sixth or seventh decades of life. It is commonly labelled as an indolent curable tumour if treated early by radical orchiectomy. The role of lymphadenectomy, adjuvant radiotherapy or chemotherapy is unclear. This case report concerns a young 38-year-old man who suffered from a painless firm left hemiscrotal mass for the past two years. Ultrasonography showed an intrascrotal paratesticular mass. Metastatic workup was negative. Left radical orchiectomy was performed and histopathology of the surgical specimen revealed leiomyosarcoma of the spermatic cord. ---Continue